Computer Implementation of 2-D Descriptor for Airplane Trajectory - Tawfeeq, Jamal F; Obaid, Mohammed Hussien; Jaseem, Ruaa Nahi (Al-Nahrain Journal of Science, 2018)
The aim of this paper is to develop a description program to stimulate movement object on a map. It’s consisting of two parts: the first part is drawing the map by using map projection (cylinder method). The second part is stimulating the autopilot movement on the map by using azimuth equation, which is showing the movement of object on the map. The static speed was taken in consideration while neglected the effects of winds, weather and other factors that affected the plane and has kept on the movement and how to perform traffic on the line of flight.